Effect of chromium, cadmium and mercury on the gill histology of Clarias batrachus L. (Chittagong University Journal of Biological Sciences, 2013)
Effect of cadmium (Cd), chromium (Cr) and mercury (Hg) on the gill histology of Clarias batrachus L. was investigated following 28 days exposure to their sublethal concentrations under laboratory condition. Hyperplasia and hypertrophy of the lamellar epithelium, necrosis, partial lifting of epithelial layer, damage of gill ray, oedema of primary lamellae, damage of pillar cells and congestion of blood vessels were the main histopathological changes. In Cd treated fishes the interlamellar spaces were abolished but distended gill rays were characteristics of Cr treatment. Extensive cellular and tissue damages were prominent in Hg treated fishes. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13383 The Chittagong Univ. J. B. Sci.,Vol. 4(1 &2):13-23, 2009